PATTERNS AND DYNAMICS OF INTERACTIVE COMMUNICATION ON RADIO AQILA 102.6 FM MEDAN - Winda Kustiawan; Hikmatul Fadilah; Muhammad Andra Syahputra; Muhammad Fairuz Attaya; Rizky Rahman Alfiris; Zakaria Musa Lubis; Rahma Aulia Sukma Purnama (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The development of digital media has encouraged radio as a conventional broadcasting medium to adapt through interactive communication practices with listeners. This study aims to analyze the patterns and dynamics of interactive communication implemented by Radio Aqila 102.6 FM Medan in building relationships with listeners. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, broadcast observations, and documentation of radio interactive communication activities, both through on-air broadcasts and digital media. The results of the study indicate that Radio Aqila 102.6 FM Medan's interactive communication takes place in a limited two-way pattern, where radio still holds dominant control over the communication flow. The dynamics of interactive communication are influenced by management policy factors, broadcaster competence, and the use of digital media that has not been optimally integrated. This study concludes that radio interactive communication is not yet fully dialogic and participatory, so a more planned communication strategy is needed to increase listener engagement on an ongoing basis.